The concept, nature and types of crime migration (Journal of actual problems of jurisprudence, 2018)
The article attempts to generate categorical and conceptual apparatus of migration crime, accompanying the migration process, the allocation of a certain set of attributes and an attempt to present a migration crime in the form of a definition. Migration crime acts as a specific subsystem of crime in general, are closely related. Vector directional migration of crime give migrants. Migration crime exists as a certain integrity, consisting of separate elements, allocated on the basis of a single criterion – the characteristics of the behavior of the subject of the crime of violation of immigration legislation or migration.Key words: migration crime, criminal migration, crime associated with migration, crime migrants, criminality of foreigners.